2012
DOI: 10.7863/jum.2012.31.8.1179
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Radial Systolic Dysfunction in Diabetic Patients Assessed by Myocardial Acceleration Derived From Velocity Vector Imaging

Abstract: Objectives The purpose of this study was to determine whether left ventricular (LV) radial systolic dysfunction occurred in diabetic patients with a normal left ventricular ejection fraction (LVEF) and impaired longitudinal contraction. Methods Velocity vector imaging was performed in 22 patients with type 2 diabetes without microangiopathy (12 men and 10 women; mean age ± SD, 49 ± 7 years), 21 patients with microangiopathy (12 men and 9 women; mean age, 50 ± 6 years), and 21 healthy control participants (11 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, this inconsistency may be explained on the basis of the restrictive inclusion criteria as the patients in the aforementioned pediatric studies and also in our study were relatively younger with short duration of DM and no diabetic complications. Several studies have recently reported that isolated diastolic dysfunction is rare and is usually associated with subclinical systolic dysfunction . Different studies have demonstrated that subtle abnormalities in longitudinal function of the LV can be identified using tissue Doppler imaging and 2DSTE in adult diabetic patients with a normal LV ejection fraction .…”
Section: Discussionmentioning
confidence: 99%
“…However, this inconsistency may be explained on the basis of the restrictive inclusion criteria as the patients in the aforementioned pediatric studies and also in our study were relatively younger with short duration of DM and no diabetic complications. Several studies have recently reported that isolated diastolic dysfunction is rare and is usually associated with subclinical systolic dysfunction . Different studies have demonstrated that subtle abnormalities in longitudinal function of the LV can be identified using tissue Doppler imaging and 2DSTE in adult diabetic patients with a normal LV ejection fraction .…”
Section: Discussionmentioning
confidence: 99%
“…The beta cells, due to their continued workload, die and thus, in the long-term, T2D leads to T1D (Figure 3). Diabetes is associated with structural (fibrosis,55,78 apoptosis,55,79,80 angiopathy8183), functional (endothelium–myocytes uncoupling,55 impaired contractility of cardiomyocytes,75 decreased survival and differentiation of cardiac stem cells,31 diastolic and systolic dysfunction55,75,84,85), and regulatory (alteration in the levels of miRNAs29,30,86 and signaling molecules involved in glucose metabolism2,3,16,87) remodeling that leads to DCM (Figure 3). …”
Section: Pathophysiology and Remodeling In Dcmmentioning
confidence: 99%
“…DCM results in cardiac functional and structural changes, independent of hypertension, coronary artery disease, or any other known cardiac disease. The structural changes include fibrosis, apoptosis, hypertrophy of myocytes and the functional changes include systolic and diastolic dysfunction [2][3][4][5][6][7]. DCM patients do not show special clinical symptoms in the early stage which makes it difficult for early clinical diagnosis and effective treatment.…”
Section: Introductionmentioning
confidence: 98%